New Forms of Electrospun Nanofibers Applied in Cardiovascular Field - Huang, Weimin; Huo, Mengen; Cheng, Nan; Wang, Rong (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease (CVD) is one of the leading causes of death worldwide. In recent years, regenerative medicine, tissue engineering and the development of new materials have become the focus of attention this field, and electrospinning technology to prepare nanofibrous materials for the treatment of cardiovascular diseases has attracted people's attention. Unlike previous reviews, this research enumerates the experimental methods and applications of electrospinning technology combined with nanofibrous materials in the directions of myocardial infarction repair, artificial heart valves, artificial blood vessels and cardiovascular patches from the perspective of cardiovascular surgery. In the end, this review also summarizes the limitations, unresolved technical challenges, and possible future directions of this technology for cardiovascular disease applications.